Convictfish on the move: variation in growth and trophic niche space along a latitudinal gradient. (30th June 2019) - Miranda, T; Smith, J A; Suthers, I M; Mazumder, D; Cruz, D O; Schilling, H T; Searle, K; Vergés, A
Abstract: The range expansion of tropical fish into temperate waters is increasing markedly in response to climate change. Range-expanding fish encounter novel diets and environments, but we know little about how these conditions facilitate or hinder distribution shifts. Here, we quantified relative growth rate, morphometric condition and trophic niche of juvenile Acanthurus triostegus, a dominant range-expanding tropical surgeonfish, at four locations across 10° of latitude off eastern Australia. We related these metrics to differences in temperature and nutritional quality of dominant seaweeds and the epilithic algal matrix. Temperate food sources were richer in nitrogen than tropical diets. Stable isotope analysis (δ 13 carbon and δ 15 nitrogen) of fish muscle revealed a large trophic niche breadth at the highest latitude indicating a generalist foraging strategy, and more nitrogen-enriched isotopic signatures compared to tropical regions. Fish length was strongly correlated to δ 13 C in all regions, suggesting an ontogenetic shift in diet independent of latitude. Despite temperature differences of 4°C, fish growth and body condition were similar across tropical and temperate regions. These results suggest that more nutritious temperate diets may compensate for the effects of cooler water temperatures. Neither summer water temperatures nor dietary factors appear to limit the success of juvenile tropical vagrants as they continue to expand their range along eastern Australia.